Research on Low-Flammable Textile and Building Materials - Кurbanova M.A; Ismailov R.I; Lityaga A.V; Yusufxodjayeva X.S (Genius Journals, 2023)
This article presents a study of fire retardant AC and ABS obtained on the basis of orthophosphoric acid and vermiculite in the form of a suspension. The proposed suspension increases the flammability and reduces smoke formation of building and textile materials.
Keywords: Fire safety; polymer material; textile materials; fire retardant